Xenophobic and Islamophobic Rhetoric among Evangelical Opinion Leaders in the Age of Trump - Joseph Roso (Socius)
Filled with anti-immigrant and Islamophobic rhetoric and buoyed by overwhelming support from white evangelicals, Donald Trump’s campaign for the presidency shocked the world. Much media coverage and scholarship on Trump’s evangelical support implicitly bought into his populist myth of representing the “legitimate” people who ultimately forced the evangelical elite to come around to their point of view. However, little systematic research has been done investigating whether evangelical leaders changed their rhetoric on immigration and Islam following Trump’s rise to political power or if xenophobic rhetoric was already a feature of evangelical media. To address this question, the author collected a corpus of more than 45,000 articles from prominent online evangelical news Web sites and used text analysis techniques to analyze how evangelical opinion leaders discussed immigration and Islam. Evangelical opinion leaders were already using frames of threat and foreignness in their rhetoric around immigration and Islam even before Trump announced his candidacy for president, and there was little change in this rhetoric following his rise to power. These findings suggest that Trump did not instill xenophobic and Islamophobic views in his followers but instead tapped into ideas that were already prevalent in the evangelical subculture.